2004
DOI: 10.1079/phn2004641
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of nutrition services in health systems in sub-Saharan Africa: opportunities in Burkina Faso, Mozambique and Niger

Abstract: Background: In sub-Saharan Africa, underweight and micronutrient deficiencies account for an estimated 25% of the burden of disease. As the coverage of national health systems expands, increased opportunities exist to address the needs of children and women, the most vulnerable to these deficiencies, through high-quality nutrition services. Objectives: To assess health providers' knowledge and practice with regard to essential nutrition services for women and children in Burkina Faso, Mozambique and Niger, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
14
0
2
Order By: Relevance
“…In this population, poor iron status and anemia was observed in the context of a national policy for IFA supplementation among pregnant women. Continuation of this routine supplementation program, as currently implemented [15,21], is unlikely to be effective in ensuring adequate micronutrient status and improving pregnancy outcomes in this population. Considering the high prevalence of iron, zinc, vitamin A, B 12 , and folate deficiencies, and previously presented results on iodine deficiency in this study population [63], interventions to promote the strengthening of ANC, and access and adherence to nutrition and health interventions are urgently needed [64,65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this population, poor iron status and anemia was observed in the context of a national policy for IFA supplementation among pregnant women. Continuation of this routine supplementation program, as currently implemented [15,21], is unlikely to be effective in ensuring adequate micronutrient status and improving pregnancy outcomes in this population. Considering the high prevalence of iron, zinc, vitamin A, B 12 , and folate deficiencies, and previously presented results on iodine deficiency in this study population [63], interventions to promote the strengthening of ANC, and access and adherence to nutrition and health interventions are urgently needed [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…In Niger, iron and folic acid (IFA) supplements are almost exclusively available to pregnant women through antenatal care (ANC) at governmental health clinics, and policies issued by the Ministry of Public Health are in line with WHO guidelines [14]. However, a previous survey of nutrition services provided during ANC revealed that health care providers’ adherence to guidelines is inadequate, and knowledge transfer to pregnant women is limited [15]. In observed ANC consultations, only 57% of pregnant women received IFA supplements, and 38% received counseling on pregnancy-related dietary improvements [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we suggest that the existence of poor quality training programmes and academic curricula in nutrition in regions of poor quality service delivery is not a coincidence. [150][151][152][153] Many of these studies are from high-burden regions and they fi nd the training and curricula to be outdated, impractical, and misaligned with local nutrition priorities. We reiterate the conclusion of the 2008 Series that much more needs to be done to strengthen strategic and operational capacity.…”
Section: Capacity For Scale Upmentioning
confidence: 99%
“…In Burkina Faso, Niger and Mozambique, fewer than 30% of mothers were counseled (Hampshire et al. ). Reasons cited included lack of health personnel to provide the service, inaccessible child health services and poor attendance by caregivers.…”
Section: Introductionmentioning
confidence: 99%